Sistem Pendukung Keputusan Pemilihan Jurusan pada SMA menggunakan Metode Profile Matching - Anjani, Yulia Merry; Muttakin, Fitriani; Zarnelly, Zarnelly; Permana, Inggih (Journal of Computer System and Informatics (JoSYC), 2024)
Every year, in the process of selecting a new major at ABC High School, a major selection is carried out. This process requires students to identify their interests, talents, and abilities in order to make informed choices. However, this process often takes quite a long time because student data must be processed one by one using various different criteria. Apart from that, the selection of majors is currently based on the highest and lowest scores, with the highest score for the Science major and the lowest score for the Social Sciences major which is considered less efficient. To overcome this problem, the development of a Decision Support System (DSS) is proposed. able to provide recommendations for selecting majors more objectively. This research aims to develop SPK using the profile matching method, which will provide major recommendations based on certain criteria at SMA ABC. The criteria used include PPDB scores, science subject scores, social studies subject scores, mathematics scores, Indonesian language scores, psychological test results, student interests and parental preferences. Based on sample trials, this system recommends 6 students to enter the science department and 4 students to enter the social studies department. This system is expected to help students obtain education that suits their abilities and interests, as well as increase the efficiency of the majors process at SMA ABC.